2018
DOI: 10.1111/jvh.12904
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of reaching world health organization targets for hepatitis C and the cost‐effectiveness of alternative strategies

Abstract: Summary New drugs for treating hepatitis C have considerably increased the probability of being cured. Treatment uptake, however, is still low. The objectives of this study were to analyse the impact of initiatives that may increase the proportion of infected people on treatment and interventions aimed at reducing the incidence of new infection among people who inject drugs. A compartmental model for Norway was used to simulate hepatitis C and related complications. We analysed 2 different screening initiative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Seventeen studies assessed the costs and effects of screening programs and antiviral treatments: seven evaluated screening in general population or subgroup of general population, five in people who inject drugs, four in high‐risk populations and three in other populations . It is to be noted here that two studies evaluated the cost‐effectiveness of HCV screening in more than one population group (general and high‐risk population, and people who inject drugs and high‐risk population).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Seventeen studies assessed the costs and effects of screening programs and antiviral treatments: seven evaluated screening in general population or subgroup of general population, five in people who inject drugs, four in high‐risk populations and three in other populations . It is to be noted here that two studies evaluated the cost‐effectiveness of HCV screening in more than one population group (general and high‐risk population, and people who inject drugs and high‐risk population).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies included in this group were cost‐utility analysis and estimated the ICER as € per QALY gained, and one study was a cost‐effectiveness analysis with the ICER reported as € per life year saved (Table S3). One study was multi‐country and assessed the screening programs in five Eastern Europe countries .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations